1890 R.I. Acts 17, ch. 897, § 6 (Special Session, June 1890) - (:unkn) unknown (General Publisher, 1890)
Every person who shall at any time of year, take, kill or destroy any quail or partridge, by means of any trap, snare, net or spring, or who shall construct, erect, set, repair, maintain or tend any trap, snare, net, or spring for the purpose of taking, killing or destroying any quail or patridge, or who shall shoot any water fowl by means or by the use of any battery, swivel, punt or pivot gun, shall be fined for each offence, twenty dollars. Provided, however, that at such seasons as the taking, killing or destroying of such birds is prohibited by this chapter, any person may snare on his own land.
--
Keywords: HUNTING REGULATION